Iclaprim: a differentiated option for the treatment of skin and skin structure infections. Issue 11 (2nd November 2018) - Noviello, Stephanie; Huang, David B.; Corey, G. Ralph
ABSTRACT: Introduction : Iclaprim is a selective bacterial dihydrofolate reductase (DHFR) inhibitor. Although there are alternative options for the treatment of acute bacterial skin and skin structure infections (ABSSSI), iclaprim is differentiated from other available antibiotics. Areas covered : Iclaprim is under clinical development for ABSSSI. This review summarizes the mechanism of action, pharmacokinetics, microbiology, clinical development program, and the differentiation of iclaprim from other antibiotics. Expert commentary : Iclaprim has a different mechanism of action (DHFR inhibitor) compared to most other antibiotics, is active and rapidly bactericidal against Gram-positive pathogens including antibiotic-resistant pathogens, and suppresses bacterial exotoxins (alpha hemolysin, Panton Valentine leukocidin, and toxic shock syndrome toxin-1). Compared to trimethoprim, iclaprim has lower MIC90s, can be given without a sulfonamide, overcomes select trimethoprim resistance, and does not cause hyperkalemia. Iclaprim is administered as a fixed dose, does not require dose adjustment in renally-impaired or obese patients, and was not associated with nephrotoxicity in the Phase 3 pivotal REVIVE studies. Iclaprim represents a novel, alternative option for the treatment of severe skin and skin structure infections due to Gram-positive bacteria, particularly in patients at risk of acute kidney injury.